Instruments of war : weapons and technologies that have changed history - Tucker, Spencer, 1937- (ABC-CLIO, 2015)
In war, the weapons and technologies employed have direct effects on how battles are waged. When new weapons are introduced, they can dramatically alter the outcomes of warfare-and consequently change the course of history itself. This reference work provides a fascinating overview of the major weapon systems and military technologies that have had a major impact on world history. Addressing weapons as crude as the club used by primitive man to the high-tech weapons of today such as unmanned drones, Instruments of War: Weapons and Technologies That Have Changed History offers nearly 270 p.